Pengembangan media pembelajaran berbasis powtoon materi pecahan sederhana di kelas III sekolah dasar - Regina, Regina; Lidinillah, Dindin Abdul Muiz; Nuryadin, Asep (IKIP Siliwangi, 2025)
As time goes by, teachers must innovate in learning media, to provide a classroom atmosphere that suits the needs of the times, technology must be applied in learning. This research aims to find out how to design PowerPoint-based video learning media for mathematics material about simple fractions in elementary schools, so that it can be a solution to problems related to interest in learning. This research uses the Research and Development (R&D) method with the ADDIE model which includes analysis, design, development, implementation and evaluation. The target of product trials is grade III elementary school students. This research was validated by material experts, media experts and pedagogy experts. The results obtained by Powtoon-based learning video media meet the suitability value for use as learning media. From the validation results, material experts showed an average score of 96% with very appropriate criteria, media experts showed an average score of 71% with appropriate criteria, and pedagogy experts showed an average score of 73% with appropriate criteria. The student response questionnaire showed an average score of 83% with very appropriate criteria and teacher responses showed an average score of 96% with very appropriate criteria. Based on these results, it can be concluded that the Powtoon-based learning video media on simple fractions material is said to be very suitable for increasing interest in learning for class III at SDN Cicariu. Keywords: Media, Mathematics, Simple Fractions.